GROWING STUDENTS’ SPEAKING SKILL TO LEARN ENGLISH THROUGH FILMS WITH THE FUN ENGLISH TEACHING METHOD FOR SENIOR HIGH SCHOOL - Bin Rustam, Asrul; Bte Abdul, Nurdevi; Junaid (English Language Teaching Methodology, 2024)
The objective of this research is to find out students’ speaking skill through films with the fun English teaching method at SMA Muhammadiyah Makassar. The methodology of this research was a pre-experimental method. The subjects of this research were the tenth-grade students of SMA Muhammadiyah Makassar. The research instrument for data collection used in this research was the test to determine students’ speaking skill before and after treatment.  The result of this research showed that the t-test value was higher than t-table value. The t-test value of speaking skill is greater than t-table (-14.749>2.160), and the mean score of the students’ post-test (75.64) is higher than the mean score of the students’ pre-test (50.14), the mean score increased by about 25.5 points. The mean score of the post-test is higher than the mean score of the pre-test. It means that the null hypothesis (H0) was rejected while the alternative hypothesis (H1) was accepted. In other words, there is significant difference between the result of the pre-test and post-test in growing students’ speaking skill. Based on the findings, the researcher concluded that the films with the fun English teaching method grew students’ speaking skill.